IN VITRO ANTIOXIDANT ACTIVITY, IN VIVO ANTIPYRETIC AND ANTI-INFLAMMATORY ACTIVITIES OF PARONYCHIA CAPITATA L. - SOUMIA, BOUZIDI; Naima, Benkiki; Zina, Allaoua (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: The aim of this study is to evaluate the in vitro antioxidant activity of Paronychia capitata various extracts, acute toxicity, the in vivo antipyretic and anti-inflammatory activities of the n-butanol extract. Methods: The antioxidant properties were tested using 2,2-diphenyl 1-picrylhydrazyl radical scavenging and Î²-carotene linoleic acid system, the total phenolic and flavonoid contents were determined. Furthermore, anti-inflammatory activity and antipyretic activity of the n-butanol extract were assessed on male Wistar rats at the dose levels 250, 500 mg/kg body weight, using the egg albumin-induced edema, and brewer's yeast-induced pyrexia method, respectively. Results: The n-butanol extract of P. capitata had considerably the highest antiradical activity with inhibitory concentration 50 value of 8.667 Î¼g/ml. Conclusion: The experimental data demonstrated that n-butanol extract of P. capitata possess significantly remarkable anti-inflammatory and antipyretic activities compared to the standard drugs. Keywords: Caryophyllaceae, Flavonoid, Inflammation, Fever, Paronychia capitata.